Pro-environmental beliefs and behaviors: two levels of response to environmental social norms - Bertoldo, R. (2016)
One of the ways to tackle the current environmental crisis is by trying to change beliefs and behaviors through the issuance of new laws. But laws and formal norms only become effective once they are also informally valued. This paper aims at determining whether law-regulated pro-environmental beliefs and behaviors (a) have acquired social value in Brazil, as they have in Europe and (b) pertain to two different construal levels, which could help explain the persistent belief-behavior gap in the environmental field. These two objectives are addressed in two studies using self-presentation and hetero-judgment paradigms. Results confirm the proposed hypotheses and are discussed in terms of social change for sustainability.